Warren Buffett - Hagstrom, Robert (Ascent Audio, 2021)
In Warren Buffett: Inside the Ultimate Money Mind, Robert G. Hagstrom breaks new ground with a deep analysis of Buffett's essential wisdom, an intricate mosaic of wide-ranging ideas and insights that Buffett calls a Money Mind. What exactly is a Money Mind? At one level, it's a way of thinking about major financial issues such as capital allocation. At another level, it summarizes an overall mindset for successfully investing in today's fast-paced stock market, a mindset that depends on a commitment to learning, adapting, and facing down irrelevant noise. This is not a method book. It is a thinking book. Warren Buffett: Inside the Ultimate Money Mind explains the philosophies of self-reliance, stoicism, rationalism, and pragmatism and their contributions to making intelligent investment decisions. It also outlines the evolution of value investing, discusses how to develop a business-driven investing mindset, and describes the defining traits of successful active management. Lastly, it examines the surprising aspects of a Money Mind-sportsman, teacher, and artist. In short, Warren Buffett: Inside the Ultimate Money Mind helps listeners understand the building blocks that go into making a Money Mind so they can begin to incorporate its principles in the service to a life of value.
Online resource; Title from title page (viewed April 20, 2021)
Keywords: Audiobooks; Livres audio